The Blacks of premodern China - Wyatt, Don J. (Encounters with Asia., 2010)
The Blacks of Premodern China describes the earliest Chinese encounters with peoples regarded as black. It focuses on the first exposure of Chinese to blacks hailing from East Africa, chiefly from today's Somalia, Kenya, and Tanzania, who arrived in China as slaves between the seventh and seventeenth centuries C.E.